Penyelenggaraan Perlindungan dan Pengelolaan Lingkungan Hidup Berdasarkan Undang-Undang Nomor 32 Tahun 2009 Tentang Perlindungan dan Pengelolaan Lingkungan Hidup (Studi Asas Partisipatif Masyarakat) - Siregar, Lastri Palentina; Nababan, Ramsul (Universitas Pahlawan Tuanku Tambusai, 2024)
This research seeks to explore the legal assurance of community engagement and their contribution towards environmental preservation and management, as stipulated in Law Number 32 of 2009. It also examines the roles played by the head of RT and the government of Tomuan Village in Pematangsiantar City. The study adopts a qualitative descriptive research method coupled with a comparative law approach for data collection. Primary data is derived from interviews, document analysis, and observations while secondary data is sourced from laws, books, journals, and articles pertinent to the research subject. Data analysis techniques employed include data reduction, data presentation, and conclusion drawing. Ten individuals from the sub-district and residents of Bah Bolon River bank were enlisted as research informants. The research findings reveal that while legal guarantees for community participation exist in Tomuan village, they are not fully compliant with Law Number 32 of 2009 regarding Environmental Protection and Management. Furthermore, the study reveals that community participation in Tomuan Village, particularly on the banks of the Bah Bolon River, is still minimal and tends to be more of a formality in environmental matters management process. Although there have been several government efforts to involve the community through consultation and cooperation, the realization of this participation has not been optimal. Time constraints, ignorance, and lack of environmental awareness are the main obstacles to increasing the effectiveness of environmental management.